2020
DOI: 10.1177/2167479519899142
|View full text |Cite
|
Sign up to set email alerts
|

Five Rings, Five Screens? A Global Examination of Social TV Influence on Social Presence and Social Identification During the 2018 Winter Olympic Games

Abstract: This study uses social presence theory and social identity theory as theoretical frameworks to examine global social TV usage during a mega-sporting event. A total of 2,296 people from six different nations (Canada, China, Germany, Japan, Sweden, and the United States) were surveyed about their social TV usage, degree of social presence, and team identification in the week following the 2018 Winter Olympics in PyeongChang, South Korea. Primary findings illustrate that increased social TV use predicts increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…Social TV research has also widely adopted SP [36][37][38][39]. Social TV viewing refers to the act of watching TV and communicating online with others who are simultaneously watching the same content [37].…”
Section: Social Presencementioning
confidence: 99%
“…Social TV research has also widely adopted SP [36][37][38][39]. Social TV viewing refers to the act of watching TV and communicating online with others who are simultaneously watching the same content [37].…”
Section: Social Presencementioning
confidence: 99%
“…Scholars have extensively examined the influence of social media on athletes, sports organizations, and fans, particularly noting how social media can spur users to perceive social presence that elicits a feeling that one is present in a sports arena or sports bar (Biocca et al, 2003; Brown-Devlin et al, 2020; Kim et al, 2017; Lim et al, 2015). In addition to feelings of social presence, scholars have noted how fans’ connection to athletes and teams and resulting parasocial relationships fostered on social media can also provoke increased levels of reported team identification (Madsen, 2016; Meng et al, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In fact, sports fans who utilize Twitter while simultaneously watching sporting events report higher levels of enjoyment (Smith et al, 2019) and use it to express emotions (Yu & Wang, 2015). Researchers have also found that social television usage during sporting events can lead to increased measures of social presence, social capital, and perceived sociability, which thereby can influence one's level of team identification (Brown-Devlin et al, 2020). Highly identified sports fans also assign greater value to tweets, and sports organizations often prioritize creating content on Twitter in order to strengthen fans' association with the team (Williams et al, 2014).…”
Section: Sports Fans' Use Of Twittermentioning
confidence: 99%